Модели на регулација на монополското однесување на пазарот - Мамучевска, Даниела (Економски факултет, УКИМ, Скопје, 2013)
Competition policy is a set of policies and laws for prevention from firms’ market behavior which aims are restriction of market competition and are detrimental to efficiency, technological innovations and consumer surplus. This implies that each restriction of market competition is not detrimental to the economic welfare. Therefore, competition policy should be focused on those business practices which restrict market competition, increase firms’ profits and reduce the consumer surplus. The main precondition to fulfill this aim of competition policy is introduction of economic approach in the antitrust analysis and in the decision making process. By making use of economic methods and models there is provided consistency in the enforcement of antitrust regulation (precisely there are determined the criteria for intervention by competition authorities), and in this way transparency of the policy implementation is increased. Also, usage of economic approach increases credibility of competition authorities. Additional to this, enforcement of antitrust regulation based on economic approach positively influences firms’ behavior by reducing uncertainty in the business environment which may result from the inappropriate and inconsistent enforcement of the regulation. Hence, the main objective of this doctorial thesis is to offer the main elements of the methodology which is necessary to apply in the process of enforcement of regulation and design of competition policy. This is very important for countries which are in the early stages of the development and enforcement of competition policy while facing with the challenges of stimulating economic growth in their own economies at the same time facing their domestic firms with the greater competition pressure coming from the international markets. Precisely, the research made in this thesis is focused on the implementation of economic approach in the antitrust analysis in these three segments of competition policy: (i) anticompetitive agreements including agreements for joint ventures (ii) abuse of dominant position and (iii) merger regulation. A logic consequence from the application of economic approach in the antitrust analysis is evaluation of the effects of competition policy enforcement. Therefore, in this thesis a special part is devoted to the methods that are used in the effects’ evaluation. Also, this thesis has an intention to detect the weak segments in the enforcement of competition policy in the Republic of Macedonia and gives recommendations for their overcoming in order to make this policy harmonized with the EU competition policy.
Models for regulation of the monopoly behavior at the market
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Олга Градишка Теменугова.
Keywords: competition policy, antitrust regulation, competition authorities, consumer surplus, market competition, efficiency and economic approach, USA, EU